1989
DOI: 10.1111/j.1600-0773.1989.tb01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Methyl Mercury in Blood and Brain During Chronic Exposure in the Monkey Macaca fascicularis

Abstract: The disposition parameters derived from a compartmental model kinetic analysis of blood Hg levels in nonpregnant, adult female Macaca fascicularis given daily doses of MeHg did not vary with either dosage level (50, 70 or 90 micrograms MeHg/kg b.wt.day) or duration of exposure (up to 507 day). In contrast, blood clearance of Hg in pregnant females was dose-dependent; it being higher at the 90 micrograms MeHg/kg b.wt.day than at the lower dosage levels. Hg levels in the brain of adult fascicularis relative to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
4
9
1
Order By: Relevance
“…Nonhuman primates have been used extensively in previous studies of MeHg toxicokinetics and developmental neurotoxicity (Burbacher et al 1986, 1990b; Gunderson et al 1986, 1988; Rice and Gilbert 1982, 1990, 1995; Stinson et al 1989; Vahter et al 1994, 1995). The routes of administration (oral for MeHg and im injection for thimerosal-containing vaccines) were chosen to mimic the two routes of Hg exposure for humans.…”
mentioning
confidence: 99%
“…Nonhuman primates have been used extensively in previous studies of MeHg toxicokinetics and developmental neurotoxicity (Burbacher et al 1986, 1990b; Gunderson et al 1986, 1988; Rice and Gilbert 1982, 1990, 1995; Stinson et al 1989; Vahter et al 1994, 1995). The routes of administration (oral for MeHg and im injection for thimerosal-containing vaccines) were chosen to mimic the two routes of Hg exposure for humans.…”
mentioning
confidence: 99%
“…Mercury concentrations in brain tissue from the harvested whales were below the lowest observable adverse effects levels documented for primates (Berlin et al, 1975b;Evans et al, 1977;Luschei et al, 1977;Stinson et al, 1989). We would expect clinical symptoms of Hg intoxication to include the loss o f motor coordination (Bellum et al, 2012), abnormal movements and convulsions (Takeuchi et al, 1977), loss of balance (Farina et al, 2005), and reduced passive avoidance.…”
Section: Integration Of Multiple Lines Of Evidencementioning
confidence: 88%
“…The lethal concentration ofH gT in human brain tissue was 16.8 mg kg'1 ww in the cerebellum o f one individual (Eto et al, 1999). Dietary MeHg dosing studies on primate species indicated that Hg intoxication was associated with brain HgT concentrations between 6.0 and 12.0 mg kg"1 ww (Berlin et al, 1975a;Evans et al, 1977;Luschei et al, 1977;Stinson et al, 1989). Furthermore, concentrations below ~2 to 5 mg kg'1 ww were likely below thresholds o f overt MeHg intoxication in mink (Suzuki, 1979;Wobeser et al, 1976).…”
Section: Mercury Concentration and Distributionmentioning
confidence: 99%
See 2 more Smart Citations